Price adjustment in currency unions: another dimension to the endogeneity of the optimum currency area criteria? - Bleaney, Michael; Yin, Lin (Wiley, 2018)
In a rational expectations model, wages and prices should respond more to shocks in currency unions than under adjustable pegs because of the absence of exchange rate adjustment. This is an aspect of the endogeneity of the optimum currency area criteria that has been largely ignored. Empirical evidence from three currency unions tends to suggest some degree of endogeneity of price flexibility, but the rate of adjustment is slow. Self-selection into currency unions by countries with naturally greater price flexibility does not appear to be a significant factor.